The Value of GARP Investing: Evidence from the Indonesian Stock Exchange - Panji Priyanto (Universitas Negeri Malang, 2021)
The purpose of this study was to examine whether or not the GARP in selecting the stock portfolios can provide a more stable growth rate of return when compared to the value stock and growth stock as well as to examine the stock return on value stock and growth stock based on the changes in its fundamentals. The population in this study was all companies listed on the Indonesia Stock Exchange (known as IDX) in the period of 2015-2019. The samples were selected using a comparative-quantitative approach and consisted of 20 companies: seven companies included in the value stock portfolio category and ten companies included in the portfolio category. Growth stock and three companies were included in the GARP's stock portfolio category. The formation of stock portfolios in the company's fundamentals was based on price to book value ratio, price-earnings ratio, and price-earnings growth ratio. This study used the ANOVA method equipped with SPSS by performing four tests: Homogeneity of Variance, Between-Subject, Post Hoc, and Homogenous Subset test. The results of this study show that there were differences in the portfolio return of value stocks, growth stocks, and GARP stocks on the Indonesia Stock Exchange in the period of 2015-2019. Meanwhile, the GARP investment strategy was stable for the growth when compared to the value investment and growth investment in the Indonesia Stock Exchange in the period of 2015-2019. The implementation of GARP concept in managing the investment portfolios and criteria for choosing the stocks have the profitable growth, first in forming the GARP because investors in the stock market tend to expect obtaining high investment returns with a limited time horizon. The implementation of GARP concept has prevented the investors from the value trap because the GARP strategy is a hybrid solution for the growth stock and value stock, thus. The GARP investors will experience a combination of returns